2010
DOI: 10.5539/elt.v3n4p168
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Error Correction vs. Error Detection on Iranian Pre-Intermediate EFL Learners' Writing Achievement

Abstract: This study tries to answer some ever-existent questions in writing fields regarding approaching the most effective ways to give feedback to students' errors in writing by comparing the effect of error correction and error detection on the improvement of students' writing ability. In order to achieve this goal, 60 pre-intermediate English learners were randomly divided into two groups: the first one was Direct Feedback Group, receiving feedback on their writing through error correction (DFG) and the other one w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…In support for this view, the findings of previous research suggest a general agreement that CF has a positive influence on learners' performance on posttests compared to ignoring them (Abedi, Latifi, & Moinzadeh, 2010;Ashwell, 1990;Bitchener, Young, & Cameron, 2005;Fathman & Walley, 1990;Kartchava, 2012;Khatri, 2013;Russell & Spada, 2006;Sampson, 2012). For example, Russell and Spada's (2006) meta-analysis of 34 studies indicated an overall positive effect of CF.…”
Section: Literature Reviewsupporting
confidence: 56%
See 3 more Smart Citations
“…In support for this view, the findings of previous research suggest a general agreement that CF has a positive influence on learners' performance on posttests compared to ignoring them (Abedi, Latifi, & Moinzadeh, 2010;Ashwell, 1990;Bitchener, Young, & Cameron, 2005;Fathman & Walley, 1990;Kartchava, 2012;Khatri, 2013;Russell & Spada, 2006;Sampson, 2012). For example, Russell and Spada's (2006) meta-analysis of 34 studies indicated an overall positive effect of CF.…”
Section: Literature Reviewsupporting
confidence: 56%
“…To mention two recent studies, Abedi et al (2010) found that their student group that received errors detected with the codes performed better than the group that received CF in the form of corrected errors. Moreover, www.ccsenet.org/elt English Language Teaching Vol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, the investigations into it (e.g. Chandler, 2003;Erel & Bulut, 2007;Beuningen et al, 2008;Abedi, Latifi, & Moinzadeh, 2010;Lu, 2010) are still inconclusive. Beuningen et al (2008) found that direct corrective feedback is more helpful and brings long-term effects on the students' writing accuracy.…”
mentioning
confidence: 99%